Global, regional, and national burden and risk factors of ischemic heart disease, 1990–2021: an analysis of the global burden of disease study - Cheng, Quankai; Zhou, Sheng; Zhong, Haicheng; Wang, Ziming; Liu, Chang; Sun, Jingjing; Deng, Jie (Frontiers in Public Health, 2025)
BackgroundWith a rapidly growing and aging world population, ischemic heart disease (IHD) remains a major burden. This study aimed to reassess the prevalence trend of IHD from 1990 to 2021 from multiple dimensions to improve the shortcomings of the existing studies and provide a solid scientific basis for policymakers.MethodsThis study extracted data on the prevalence, incidence, mortality, disability-adjusted life years (DALYs), and associated risk factors of IHD from the global burden of disease (GBD) 2021 study. Descriptive, decomposition, and risk factor analyses were used to provide insights into the epidemiologic patterns of IHD from 1990 to 2021 and project the burden of IHD from 2022 to 2045. Potential differences in burden and risk factors based on age, sex, 21 GBD geographic regions, five social development index (SDI) regions, and 204 countries are highlighted.ResultsGlobally, the age-standardized prevalence rate (ASPR) of IHD is increasing, while the age-standardized incidence rate (ASIR), age-standardized mortality rate (ASMR), and age-standardized disability-adjusted life years (ASDR) are decreasing. ASPR, ASIR, ASMR, and ASDR were highest in the low-middle SDI regions and lowest in the high SDI regions. ASMR and ASDR were highest in Nauru and lowest in Portugal. Men had an overall heavier burden of IHD than women; the 65–69 age group had the largest burden, and those aged >95 years had the highest crude incidence rate. In addition, the burden of IHD was negatively correlated with SDI across regions and countries, while decomposition analyses suggest that the main reasons for the current increase in the burden of IHD are aging and population growth. Risk factors have changed relatively little over the 32 years, with metabolic risk still ranking first. We forecast that the absolute burden of IHD will continue to increase till 2045; however, ASIR, ASMR, and ASDR will gradually decline.ConclusionFrom 1990 to 2021, the global burden of IHD generally increased and varied across regions, sex, and age groups. Due to increasing population growth and aging, there is an urgent need for strategically directed measures to reduce the burden of IHD.